A longitudinal study on the stability of self-estimated intelligence and its relationship to personality traits. (1st February 2017) - Gold, Bernadette; Kuhn, Jörg-Tobias
Abstract: The present study investigated the stability of fluid self-estimated intelligence (SEI) directly, one, and two weeks after the administration of an IQ test in N  = 238 German high school students (tested group, TG) in comparison to N  = 316 untested high school students (control group, CG). Multigroup latent change analysis indicated that, in comparison to the CG, the TG had a significant latent decrease in SEI from before to after having taken an IQ test ( d  = 0.36), and again a significant latent increase in SEI one week later ( d  = 0.28). There was no significant difference in the change from the first and the second week after the IQ test. Results further showed that more accurate SEI was obtained only directly after IQ test participation, but not one or two weeks later, possibly due to self-serving processes. Additionally, we found that extraverted persons displayed a substantially lower decrease in SEI from pre- to posttest, and their SEI rebound effect between posttest and follow-up was significantly smaller. Highlights: SEI significantly decreased after taking an IQ test and increased one week later. More extraverted persons had a smaller decrease in SEI after the IQ test. People more open to experiences had a significantly higher rebound effect. Agreeableness had no significant effect on any change in SEI.